Outcomes of Using Heart Sound Simulator in Teaching Cardiac Auscultation (Canadian Medical Education Journal, 2010)
Background - Despite continued curriculum reform, the clinical skills competencies of medical graduates at all levels are steadily declining within a training system, where bedside opportunities become a luxury and the laboratory tests prevail over the clinical skills. While high-fidelity expensive simulators are being embraced by high-procedure volume specialties, low-fidelity and relatively inexpensive simulators, such as the heart sounds simulators remain under-utilized in medical training.  Methods - We used a commercially available heart sound synthesizer in 2-hour training sessions with students and residents. Pre-post testing was completed at the beginning of the training session and three weeks after the session; participant responses were recorded by audience interactive response system.  Results - Data analysis was accomplished with statistical software SPSS 17.0 utilizing paired t-test, and showed a statistically significant difference in learners’ knowledge and skills attainment 3 weeks after completion of the simulation training (p